Injuries in Padel players: What is known? A scoping review - Giustino, V.; Figlioli, F.; Patti, A.; Vicari, D. S. S.; Alamia, G.; Palma, A.; Romualdo, C. -L.; Thomas, E.; Bianco, A. (International Journal of Sports Science & Coaching, 2024)
Background Padel has spread rapidly in several countries around the world. Although this racket sport seems to have several health benefits, the number of scientific papers on this sport is still very few. This scoping review aimed to systematically map the evidence regarding injuries in Padel players by identifying, synthesizing, and assessing the studies currently existing in the scientific literature. Methods This scoping review was conducted following the guidelines provided by the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews and the Population, Concept, Context framework was adopted. Articles were collected from PubMed, Web of Science, and Scopus. Results A total of seven studies were included in this review. The most frequent injury location is in the elbow, followed by shoulder, and low back. As for lower limbs, knee represents the most affected body region. Although not all the studies included described the type of injuries, tendon, joint, and muscle are the body structure most injured. Conclusion This scoping review can aid in a better comprehension of the location and type of injuries that occur in Padel players. However, it is worth noting that all the studies existing concerns nonprofessional athletes. Hence, these findings could be useful to coaches as they add knowledge on the risk of injury in padel that can allow the planning of suitable training programs for amateur and recreational players in order to prevent injuries.